Preparation and Characterization of Titanium Dioxide/ Poly(methyl methacrylate) Composites by in-situ Polymerization - Li, Meng; Yang, Benhong; Wu, Yun; Yu, Tongzhong (Asian Journal of Chemistry, 2013)
Anatase titanium dioxide (TiO2) particles were obtained by sol-gel method and modified with saline coupling agent. TiO2/poly(methyl methacrylate) composites were prepared via in situ bulk polymerization of methyl methacrylate, in which modified TiO2 particles were dispersed uniformly. SEM micrographs showed that TiO2/poly(methyl methacrylate) composites exhibited favourable miscibility behaviour, even at high content of TiO2 (0.7 wt %). Moreover, incorporation of TiO2 particles can improve mechanical and thermal stability of poly(methyl methacrylate) significantly.